Topical corticosteroid-induced rosacea-like dermatitis – report of cases and review of the literature - Sielska, Halina; Kłujszo, Elżbieta (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction. Topical corticosteroid-induced rosacea-like dermatitis (TCIRD) is presently classified as a separate entity. In 98% of cases it is the result of rebound phenomenon after treatment with corticosteroids. Objective. Presentation of side effects of topical glucocorticosteroids applied on the facial skin lesions. Case reports . We present 9 cases of female patients, who developed TCIRD after prolonged use of topical cortricosteroids. We discuss methods of treatment and management of patients who may consider flare-up after corticosteroids withdrawal as ineffectiveness of applied medications or as their undesirable side effects. Conclusions . Uncontrolled, long-term topical corticosteroid treatment of skin lesions localized on the face may lead to development of TCIRD. The management of these patients is difficult because of flare-up of skin changes after corticosteroids withdrawal at the first stage of therapy.